New spirits of capitalism crises, justifications, and dynamics - Du Gay, Paul.; Morgan, Glenn (Oxford : Oxford University Press, 2013)
This text explores the nature and effects of contemporary capitalism through engaging with Boltanski and Chiapello's seminal text, 'The New Spirit of Capitalism'. It provides a comprehensive overview and interrogation of the text and develops new insights into contemporary neo-liberal or 'financialized' capitalism.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Boltanski, Luc; Capitalism; Capitalism -- Political aspects